Dissemination of original NMR data enhances reproducibility and integrity in chemical research. Issue 9 (20th May 2016) - Bisson, Jonathan; Simmler, Charlotte; Chen, Shao-Nong; Friesen, J. Brent; Lankin, David C.; McAlpine, James B.; Pauli, Guido F.
Abstract : Discusses the relevance of freely accessible raw NMR data, published with articles and/or in unified databases, as part of good research practices promoting accuracy, transparency, and reproducibility of bio-chemical outcomes. Abstract : The notion of data transparency is gaining a strong awareness among the scientific community. The availability of raw data is actually regarded as a fundamental way to advance science by promoting both integrity and reproducibility of research outcomes. Particularly, in the field of natural product and chemical research, NMR spectroscopy is a fundamental tool for structural elucidation and quantification (qNMR). As such, the accessibility of original NMR data, i.e., Free Induction Decays (FIDs), fosters transparency in chemical research and optimizes both peer review and reproducibility of reports by offering the fundamental tools to perform efficient structural verification. Although original NMR data are known to contain a wealth of information, they are rarely accessible along with published data. This viewpoint discusses the relevance of the availability of original NMR data as part of good research practices not only to promote structural correctness, but also to enhance traceability and reproducibility of both chemical and biological results.